New Screening Proposals: the Federal Joint Commission Defines the Parameters for Cervical Cancer Screening from 2018 Statement of the Gynecology Oncology Working Group (AGO) - Hillemanns, P.; Mallmann, P.; Beckmann, Matthias (Geburtshilfe und Frauenheilkunde, 2016)
The Gynecology Oncology Working Group (AGO e.V.) unequivocally welcomes the decision taken by the German Federal Joint Commission (Gemeinsamer Bundesausschuss, G-BA) on March 19, 2015 regarding screening for cervical cancer. AGO is convinced that, in view of recent medical advances, this evidence-based decision will improve screening for cervical cancer.
EVALuna2:32998